2020
DOI: 10.3389/fmars.2020.00642
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Niche and Diversity of a Pelagic Squid (Dosidicus gigas): A Comparative Study Using Stable Isotope, Fatty Acid, and Feeding Apparatuses Morphology

Abstract: Commercially important pelagic squid such as jumbo squid Dosidicus gigas play a key role in energy and nutrient transfer in marine ecosystem. Geographic variations in the foraging strategy of D. gigas can provide valuable information on cephalopod trophic diversification and adaption to natural and anthropogenic impacts. Here, we used a novel combination of stable isotope (SI) and fatty acid (FA) analyses of muscle tissues and morphometric measurements of feeding apparatuses to evaluate spatial patterns of hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
(92 reference statements)
2
13
0
Order By: Relevance
“…The strategy of energy acquisition for reproduction is independent from body size that has been considered as an important factor linked to feeding ability [ 15 , 25 ]. LMMs results indicated that reproductive energy was not correlated with mantle length (Additional file 1 : Tables S2, S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of energy acquisition for reproduction is independent from body size that has been considered as an important factor linked to feeding ability [ 15 , 25 ]. LMMs results indicated that reproductive energy was not correlated with mantle length (Additional file 1 : Tables S2, S3).…”
Section: Discussionmentioning
confidence: 99%
“…Such energy expenditures should theoretically be saved when the consumer forages for small prey species to gain a comparative energy resource [ 24 ]. It is also assumed that the reason why squid species shift feeding habits ontogenetically is because they become better at hunting as they grow rather than the increased need of energy for reproduction [ 15 , 25 ]. It is still unclear how reproductive energy needs are met for semelparous animals, which is important for understanding their life-history.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with δ 2 H, fatty acid profiles confirm diet differences among species across locations and can be used to infer diet quality. We created a matrix for δ 2 H values of feathers and relative abundance of 8 notable plasma fatty acids (palmitic acid, stearic acid, oleic acid, LA, ALA, ARA, EPA, and DHA) that were standardized (Routti et al, 2012;Gong et al, 2020) to a mean of zero and a standard deviation of one using the vegan R package (Oksanen et al, 2019). Using Euclidean distances, a redundancy analysis compared δ 2 H values and FA percentages among species and between locations using the vegan package.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The isotope analysis in squids has been performed using mantle muscle tissue [17,[29][30][31] beaks [32][33][34][35][36], gladii [37][38][39], statoliths [40], and eye lenses [41][42][43]. Each tissue allows the isotope analysis in a determinate time; two months approximately for muscle tissue, and life history for beaks, gladii, and eye lenses [29,41,44].…”
Section: Introductionmentioning
confidence: 99%